An Adherence-Enhancing Program Increases Retention in Care in the Swiss HIV Cohort. (13th August 2020) - Kamal, Susan; Glass, Tracy R; Doco-Lecompte, Thanh; Locher, Sophie; Bugnon, Olivier; Parienti, Jean-Jacques; Cavassini, Matthias; Schneider, Marie P
Abstract: Background: This study tested a theory-based adherence-enhancing intervention: the "Interprofessional Medication Adherence Program" (IMAP) to increase human immunodeficiency virus (HIV) retention in care. Methods: We retrospectively compared our intervention center (intervention group [IG]) with a standard of care center (control group [CG]) both participating in the Swiss HIV Cohort Study between 2004 and 2012. Endpoints were defined as >6-month and >12-month gaps in care for intervals of care longer than 6 and 12 months without any blood draw. Inverse probability of treatment weights was used to adjust for differences between patients at the 2 centers. Viral failure was defined as ribonucleic acid ≥50 copies/mL after 24+ weeks on antiretrovirals. Results: The IG included 451 patients, CG 311. In the IG, 179 (40%) patients took part in the IMAP for a median of 27 months (interquartile range, 12–45). Gaps in care of ≥6 months were significantly more likely to happen in the CG versus IG (74.6% vs 57%, P < .001). The median time until the first treatment gap was longer in the IG vs CG (120 vs 84 weeks, P < .001). Gaps in care of ≥12 months evaluated in 709 (93%) patients were significantly more likely to occur in the CG compared with the IG (22.6% vs 12.5%, P < .001). The rate of viral failure was significantly lower in the IG (8.3% vs 15.1%, P = .003). Conclusions: This study, in a real-world setting, shows the effectiveness of the IMAP to reduce 6- and 12-month gaps in follow up among people with HIV. These results should be confirmed by studies in other settings. Abstract : This study shows the effectiveness of a theory-based interprofessional medication adherence program to increase retention in care. The program significantly reduced gaps in follow up over 6- and 12-month periods in a large cohort of people with HIV.